Insights on non-performing loans: evidence from Zimbabwean commercial banks in a dollarised environment (2009-2012) - Chikoko, Laurine; Mutambanadzo, Tendekayi; Vhimisai, Takaiona (Scholarlink Research Institute Journals, 2016)
This study was prompted by the gradual deterioration in asset quality in most commercial banks in Zimbabwe after the adoption of the multiple currency exchange rate regime. The poor asset qualities were reflected by the non-performing loans trending towards the watch list category. In this regard we investigated the commercial bank credit process with the objective of understanding the fundamental causes of the impaired assets that are bedeviling the Zimbabwean banking sector so that some of the mistakes are not repeated and correctional measures are put in place. The methodology adopted a survey research design with use of questionnaires and interviews with commercial banks head credit risk, head retail and head corporate banking division from 15 registered commercial banks in Zimbabwe. Research findings show that some banks were sitting on nonperforming loans due to poor credit analysis processes; wrong products offered to the clients; lending based on balance sheet strength instead of cash flow based lending; banks taking too much comfort in security; information asymmetry leading to moral hazard; economic environment and political influence. Key recommendations include an urgent setting up of the Credit Bureau; banks should not adjust clients request and the need for banks to consider the economic environment and adjust their credit culture. The central bank needs to tighten its supervisory role and ensure prudential guidelines are not violated.